Training military institutions cadets for professional-communicative activities with the help of task-based learning. - Svitlana Zhytska (National Technical University of Ukraine "Kyiv Polytechnic Institute", 2014)
The article deals with the importance of the task-based teaching usage for formation of cadets' professional communicative competence as well as the role of learner-centered approach in teaching foreign languages. Special attention is paid to the concepts of "task" and "effective task". Types and sequence of communicative tasks that can be used in foreign language training for professional communication are defined. Classes using the task-based teaching are described as a cycle of three stages; the characteristic features of each stage are provided. The difference between traditional lessons, where "Presentation-Practice-Production" method is used, and task-based learning is considered. The article describes the advantages and disadvantages of using the task-based learning in teaching foreign languages to cadets of higher military educational institutions. The article defines the classification of tasks and basic stages of lessons using the task-based learning. It emphasizes the need to develop learners' independence and cadets' creativity. Task-based learning allows taking into account cadets' needs while studying foreign languages. The article highlights the importance of the task-based learning to use a foreign language in real-life situations. In addition, the importance of content but not the form of utterances is determined, as it brings cadets to successful task completion which is the main purpose of task-based learning.